ANALISIS NILAI KEARIFAN LOKAL DALAM NOVEL KAWI MATIN DI NEGERI ANJING KARYA ARAFAT NUR - Wahidah Nasution; Yusrawati Jr Simatupang; Rika Kustina (Universitas Negeri Medan, 2022)
The novel is an essay that tells about human life and the surrounding community. Messages about the value of local wisdom can be found in novels, especially novels that are about culture and anthropology. The novel entitled Kawi Matin di Negeri Anjing is a novel set in Aceh so that this novel implies a lot of depictions of the life of the Acehnese people. The formulation of the problem is how are the values of local wisdom contained in the novel Kawi Matin in the Land of Dogs by Arafat Nur. The research source comes from a novel with data in the form of words, phrases, and clauses contained in the novel. The study of the novel uses Jim Ife's theory. The findings of this study are local knowledge, local values, local skills, local resources and local group solidarity. The conclusion of the research is that the novel contains local wisdom values